PERFORMANCES AND ORGANOLEPTIC QUALITY OF VANARAJA CHICKEN UNDER DIFFERENT REARING SYSTEM - P. THIRUMURUGAN, I. A. BABA1 Y. SINGH , I.U. SHEIKH (Indian Journal of Animal Production and Management, 2017)
A total of 120 day old chicks were utilized to evaluate the production performance ofVanaraja chickens under different rearing systems viz. cage, deep litter and semi intensiveduring 2009. The overall mean body weight, feed conversion ratio were recorded as1323+28.02, 1238.12+46.02 and 1283.00+26.30 g; and 2.27, 2.44 and 2.05 for cage, deeplitter and semi intensive systems respectively. Overall feed conversion ratio (FCR), proteinefficiency ratio (PER) and energy efficiency ratio (EER) was significantly better (P